Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1136/bmj.a1518
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of skeletal fractures in child abuse: systematic review

Abstract: Objectives To systematically review published studies to identify the characteristics that distinguish fractures in children resulting from abuse and those not resulting from abuse, and to calculate a probability of abuse for individual fracture types.Design Systematic review.Data sources All language literature search of Medline, Medline in Process, Embase, Assia, Caredata, Child Data, CINAHL, ISI Proceedings, Sciences Citation, Social Science Citation Index, SIGLE, Scopus, TRIP, and Social Care Online for or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
326
2
11

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 401 publications
(350 citation statements)
references
References 18 publications
3
326
2
11
Order By: Relevance
“…15,49,50 In contrast, supracondylar fractures in ambulatory children are usually noninflicted injuries resulting from short falls. 15 Physicians should also be aware of a particular mechanism reported to produce a noninflicted spiral-oblique fracture of the humerus in 1 case report. 51 When the young infant was rolled from the prone position to the supine while the child' s arm is extended, the torsion and stress placed on the extended arm appeared to cause a spiral-oblique fracture of the midshaft of the humerus.…”
Section: Common Fractures With Low Specificity For Child Abusementioning
confidence: 99%
See 3 more Smart Citations
“…15,49,50 In contrast, supracondylar fractures in ambulatory children are usually noninflicted injuries resulting from short falls. 15 Physicians should also be aware of a particular mechanism reported to produce a noninflicted spiral-oblique fracture of the humerus in 1 case report. 51 When the young infant was rolled from the prone position to the supine while the child' s arm is extended, the torsion and stress placed on the extended arm appeared to cause a spiral-oblique fracture of the midshaft of the humerus.…”
Section: Common Fractures With Low Specificity For Child Abusementioning
confidence: 99%
“…Rib fractures have high probability of being caused by abuse. 15,17,21 The positive predictive value of rib fractures for child abuse in children younger than 3 years was 95% in one retrospective study. 22 Other less common causes of rib fractures in infants include significant trauma sustained during childbirth or a motor vehicle crash as well as minor trauma in infants who have increased bone fragility.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 They occur in infants and toddlers (under three years old) who cannot give a causal explanation about the fracture, and the incidence is around 78%. Worlock and colleagues studied children under 12 years old and showed that 80% of all fractures from abuse are seen in children under 18 months, contrary, 85% of fractures not caused by abuse occurred in children over 5 years.…”
Section: Introductionmentioning
confidence: 99%